STUDI ETNOGRAFI TENTANG PENGARUH PEMBELAJARAN INTERAKTIF TERHADAP KETERLIBATAN SISWA DALAM PEMBELAJARAN BAHASA ARAB DI MAN 2 WONOSOBO - Tsalitsa Nuurun Muntadziroh; Taliya Farkhah; Muhammad Yakut Bainal hajar (DAS Institute, 2026)
This study aims to examine the impact of implementing interactive learning models on student engagement in Arabic language learning at MAN 2 Wonosono. The approach used is qualitative with the type of indirect field study. Data collection techniques were conducted through indirect observation, using observation guides to record student activities and interactions during the learning process. The results show that the interactive learning model has a positive impact on student engagement. Students become more active in participating, discussing and responding during the learning process. In addition, the diversity of students' social conditions also enriches the learning dynamics, creating a collaborative and inclusive atmosphere. Overall, this model is effective in increasing student engagement, especially in Arabic language learning, while providing new insights in developing learning strategies that are relevant to students' needs.